Komunikasi Berbahasa Jawa pada Remaja Perspektif Fenomenologi Alfred Schutz - Salsabilla Yoga Destrilia; Joko Sutarso (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2026)
The shift in regional language use among adolescents has predominantly been examined from a sociolinguistic perspective, emphasizing language frequency and the factors driving language shift. However, limited attention has been given to adolescents’ subjective experiences in constructing the meaning of regional language use. This study aims to explore the meaning of Javanese language communication among adolescents in Blimbing Village, Sambirejo District, Sragen Regency through Alfred Schutz's phenomenological perspective. A qualitative phenomenological approach was employed involving eight adolescent informants and two parents selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, then analyzed using phenomenological procedures. The findings reveal that adolescents construct Javanese as a cultural identity, a medium for maintaining social relationships, and a cultural heritage worthy of preservation. These meanings emerge from the stock of knowledge developed through everyday interactions with family, peers, and the surrounding community. Furthermore, adolescents’ language choices are influenced by motives rooted in past experiences and in-order-to motives oriented toward achieving communication effectiveness while preserving social harmony. Although Indonesian is increasingly dominant in educational, peer, and digital communication contexts, this shift reflects communicative adaptation rather than the erosion of cultural identity. This study contributes to communication and phenomenological research by demonstrating that the sustainability of Javanese is shaped not merely by the frequency of language use but by the meanings constructed through adolescents' lived experiences and intersubjective social interactions. Keywords: Javanese language, phenomenology, Alfred Schutz, cultural identity, adolescents